ASSOCIATIAON BETWEEN ADROPIN AND ATHEROSCLEROSIS IN HYPERTENSIVE PATIENTS WITH CONCOMITANT TYPE 2 DIABETES MELLITUS AND OBESITY - Shelest, Boris (Medicinski časopis, 2018)
Hypertension (HTN) and diabetes mellitus 2 type (2TDM) are considered as risk factors for atherosclerosis and cardiovascular diseases. Our study suggests that a hormone peptide, called adropin, is involved in the processes of atherosclerotic vessels’ damage in hypertensive patients with T2DM and obesity. As inflammation also suggested being involved in atherosclerosis processes, we studied the IL-6 concentration in enrolled patients. We assessed the links between atherosclerosis intensity and adropin concentration in patients with combination of HTN and 2TDM with obesity. A group of hypertensive patients with 2TDM and obesity (n=99) was prospectively enrolled into the study. The serum IL-6 and adropin levels were measured by ELISA, and the atherosclerosis marker was carotid intima media thickness. Patients were divided on with atherosclerosis (CIMT≥0.9mm) group 1 (n=69), and without atherosclerosis (CIMT